2009
DOI: 10.1080/08870440802040277
|View full text |Cite
|
Sign up to set email alerts
|

The experience of attending a lay-led, chronic disease self-management programme from the perspective of participants with multiple sclerosis

Abstract: A lay-led, community-based intervention, the Chronic Disease Self-Management Course (CDSMC) is effective for a range of long-term health conditions (e.g. arthritis, heart disease). However, the perceived value and experience of the CDSMC for people with Multiple Sclerosis (MS) has not been examined. The present qualitative study addressed this omission. Ten participants with MS (7 female; age range 35 to 60 years; disease duration 4 to 19 years) were interviewed before attending the CDSMC and at 4-month follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 32 publications
2
63
0
Order By: Relevance
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…Having discussed the 17 disagreements, we agreed that five studies on which there was disagreement would be included. 100,103,110,116,134 An additional four studies were identified through reference checks and efforts to locate published literature linked to unpublished work identified through the electronic search. 111,112,135,136 An additional two papers (women only), although individually ineligible, were located as 'linked papers' for two of the original 34 studies, 114,120 giving a total of 38 studies (reported in 44 papers), as shown in Figure 8.…”
Section: Search Outcomementioning
confidence: 99%
“…In addition, realistic goal setting was linked to the successful planning and performing of activities that participants had avoided in the past (Barlow et al, 2009). Similarly, women with MS in another self-management study reported that setting goals with incremental steps helped them formulate their goals and monitor achievement over time (Stuifbergen et al, 2003).…”
mentioning
confidence: 99%
“…Goal setting is a technique that is often taught during self-management programs for people with chronic illness to facilitate such behavioral changes (Von Korff, Gruman, Schaefer, Curry, & Wagner, 1997). Goal setting has been examined in previous MS-specific studies based in inpatient rehabilitation settings (Bloom et al, 2006;Khan, Pallant, & Turner-Stokes, 2008) and in community-based self-management programs (Barlow, Edwards, & Turner, 2009;Stuifbergen, Becker, Timmerman, & Kullberg, 2003). In inpatient rehabilitation studies, goal setting is often directed by clinicians and commonly focuses on symptom management (Bloom et al, 2006;Khan et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation